Caloric restriction reduces trabecular bone loss during aging and improves bone marrow adipocyte endocrine function in male mice - Charlotte Rinne; George A. Soultoukis; George A. Soultoukis; Masoome Oveisi; Masoome Oveisi; Marina Leer; Marina Leer; Oskar Schmidt-Bleek; Lisa-Marie Burkhardt; Lisa-Marie Burkhardt; Christian H. Bucher; Eman Abou Moussa; et al. (Frontiers in Endocrinology, 2024)
IntroductionCaloric restriction (CR) is a nutritional intervention that increases life expectancy while lowering the risk for cardio-metabolic disease. Its effects on bone health, however, remain controversial. For instance, CR has been linked to increased accumulation of bone marrow adipose tissue (BMAT) in long bones, a process thought to elicit detrimental effects on bone. Qualitative differences have been reported in BMAT in relation to its specific anatomical localization, subdividing it into physiological and potentially pathological BMAT. We here examine the local impact of CR on bone composition, microstructure and its endocrine profile in the context of aging.MethodsYoung and aged male C57Bl6J mice were subjected to CR for 8 weeks and were compared to age-matched littermates with free food access. We assessed bone microstructure and BMAT by micro-CT, bone fatty acid and transcriptomic profiles, and bone healing.ResultsCR increased tibial BMAT accumulation and adipogenic gene expression. CR also resulted in elevated fatty acid desaturation in the proximal and mid-shaft regions of the tibia, thus more closely resembling the biochemical lipid profile of the distally located, physiological BMAT. In aged mice, CR attenuated trabecular bone loss, suggesting that CR may revert some aspects of age-related bone dysfunction. Cortical bone, however, was decreased in young mice on CR and remained reduced in aged mice, irrespective of dietary intervention. No negative effects of CR on bone regeneration were evident in either young or aged mice.DiscussionOur findings indicate that the timing of CR is critical and may exert detrimental effects on bone biology if administered during a phase of active skeletal growth. Conversely, CR exerts positive effects on trabecular bone structure in the context of aging, which occurs despite substantial accumulation of BMAT. These data suggest that the endocrine profile of BMAT, rather than its fatty acid composition, contributes to healthy bone maintenance in aged mice.